2016
DOI: 10.1037/xhp0000141
|View full text |Cite
|
Sign up to set email alerts
|

Linking melodic expectation to expressive performance timing and perceived musical tension.

Abstract: This research explored the relations between the predictability of musical structure, expressive timing in performance, and listeners' perceived musical tension. Studies analyzing the influence of expressive timing on listeners' affective responses have been constrained by the fact that, in most pieces, the notated durations limit performers' interpretive freedom. To circumvent this issue, we focused on the unmeasured prelude, a semi-improvisatory genre without notated durations. In Experiment 1, 12 profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 89 publications
2
46
0
Order By: Relevance
“…Furthermore, influential proposals have postulated close ties between expectation and both emotional responses to music (Huron, 2006) and musical meaning (Meyer, 1957). Regarding tension, melodic expectation has recently been linked to expressive performance, which in turn was linked to perceived tension (Gingras et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, influential proposals have postulated close ties between expectation and both emotional responses to music (Huron, 2006) and musical meaning (Meyer, 1957). Regarding tension, melodic expectation has recently been linked to expressive performance, which in turn was linked to perceived tension (Gingras et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It was designed for modeling dynamically changing auditory expectations, based on long-term and short-term statistical learning, which evolve as a piece of music unfolds. Empirical research has demonstrated that IDyOM accurately simulates listeners' predictive processing of melody in many perceptual tasks involving pitch expectation (Pearce, 2005; Pearce et al, 2010; Omigie et al, 2012, 2013), uncertainty (Hansen and Pearce, 2014), segmentation (Pearce et al, 2010) and emotional response (Egermann et al, 2013; Gingras et al, 2015). …”
Section: The Probabilistic Modelmentioning
confidence: 99%
“…Gingras et al . report a study that examines the relationship between compositional structure, expressive performance timing, and perceived tension in this communicative process . IDyOM was used to characterize, in terms of IC and entropy, the compositional structure of the Prélude non mesuré No.…”
Section: Probabilistic Prediction In Music Cognitionmentioning
confidence: 99%
“…This enables successful communication of musical meaning between composers and performers and between performers and listeners. 2,[5][6][7][8] Unlike many other general theories of music cognition, [9][10][11][12] this approach elegantly encompasses the idea that listeners exposed to different musical styles will differ in their psychological processing of music. It provides naturally for musical enculturation, the process by which listeners internalize the regularities and constraints defining and distinguishing musical styles and cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In such models lags of predictors up to five seconds in duration and beyond are required for optimal models. Furthermore, research implementing Markov chain models of musical structure and perception report similar results [60]. Thus we assessed whether using the same acoustic predictors measured solely over the last five seconds of each perceived phrase could result in models that were as good or even better than those obtained from the whole-phrase trajectory.…”
Section: Resultsmentioning
confidence: 94%